Internalization of Islamic Values and Piousness of Daqu Primary School Students Based on Tahfidz and National Curriculum - Sholihah, Hidayatus; Zaenurrosyid, Ahmad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2025)
This study discusses the model of internalizing Islamic values and students' morals through the This study discusses the internalization model of Islamic values and morals of students through the integration of Daqu Method learning in the integrated curriculum at Primary Daqu School at Semarang, Central Java. The Daqu Method, which prioritizes the balance between intellectual, spiritual, and emotional intelligence, is the main approach in shaping the character of students. The research method used is a qualitative approach with a case study at Primary Daqu School. Data collection techniques include observation, in-depth interviews, and documentation. The findings reveal that the internalization of Islamic values and morals is carried out through three main aspects: exemplary-based learning (uswah hasanah), habituation in daily activities, and value integration within subjects. Teachers play a crucial role as primary role models in shaping students' character through compassionate interactions and an Islamic values-based approach. Additionally, a conducive school environment supports the internalization process, such as the culture of tahfiz, congregational prayers, and the implementation of honesty, discipline, and social care values in every school activity. By applying the Daqu Method in the integrated curriculum, students not only acquire academic knowledge but also develop a strong religious understanding and good morals.